INOVATION OF PANNACOTA DAIRY FREE - Farrah Farrah (Akademi Pariwisata Bunda Mulia, 2023)
Purpose Porang flour from porang tubers (Amorphophallus muelleri Blume) has a soluble food fiber content whose structure and function are similar to pectin called glucomannan. The content of glucomannan contained in porang tubers is very large namely as a gelling agent, which can be one of the alternative thickeners or stabilizers in solution and dough and can replace gelatin milling on pannacotta cake vegan. This research aims to find out the usefulness and success rate of porang flour in replacing gelatin in the manufacture of vegan Pana cotta Cake. It also aims to find new alternative gelatin substitutes on the market that many use pig base materials in the manufacture of gelatinDesign/methodology/approach —.. This research uses qualitative descriptive methods, intending to know the process of making Pana cotta Cake with porang flour and knowing the quality of Pana cotta Cake with gelatin substitution with porang flour from perspective experts in the field of food product to conformity with panna cotta cake standards.Not only that, the glucomannan content in porang tubers can also be an alternative thickener or stabilizer in solutions and doughs and can replace the use of gelatinFindings — Based on the overall results of the study, reviewed from the quality aspects of the foods studied, the researchers concluded that Panna Cotta Vegan with porang flour was favored by the panelists and had good value. Then, porang flour proved to be a substitute alternative to gelatin in the manufacture of Panna Cotta especially Panna Cotta Vegan.Practical implications — For advice, it should be noted during the process of making Panna Cotta which is stirred slowly until boiling, then be sure to discard the froth that is on top of the panna cotta and use the technique of placing a spoon on top of the mold in an upside down position to avoid creating froth. For further research, researchers hope to be able to develop a wide range of processed products by using additional ingredients of porang flour and focus on raising awareness using existing local potentialKeywords — Food Inovation, Pannacota, Dairy free